A Computational Experiment of the Endo versus Exo Preference in a Diels–Alder Reaction - Rowley, Christopher N; Woo, Tom K; Mosey, Nick J (Journal of chemical education, 2009)
We have developed and tested a computational laboratory that investigates an endo versus exo Diels–Alder cycloaddition. This laboratory employed density functional theory (DFT) calculations to study the cycloaddition of N-phenylmaleimide to furan. The endo and exo stereoisomers of the product were distinguished by building the two isomers in a molecular modeling program and using the Karplus equation to calculate the coupling constants for a key dihedral. A series of calculations were then performed to evaluate reaction energies and activation energies, which made it possible to distinguish between the kinetic and thermodynamic products of this reaction. Through this exercise, students are able to gain experience in several common practices in computational chemistry, such as testing a truncated model system, judging the quality of the results, and comparing different levels of theory.